Techno-economic optimization of novel stand-alone renewables-based electric vehicle charging stations in Qatar - Abdulla Al Wahedi (17115613) (2022)
One of the main challenges of e-mobility roll-out is securing the required charging demand without stressing the existing power grid. The electrical source must be non-conventional to achieve the ultimate eco-friendly goal. This study conducts a techno-economic assessment for a novel stand-alone renewables-based charging station to determine the optimal configuration to generate the required daily charging demand. The optimization is accomplished through modeling and simulating of the proposed design using HOMER software in four cities of Qatar to investigate various geographical locations and metrological conditions. The optimal solution is compared with the grid extension option in each location using a comprehensive economic criterion. The results showed that 250 kW wind turbine with 60 m hub height, 450 kWp CPV/T system, 500 kW electrolyzer, 100 kW H2 and NH3 FCs, 15 kW bio-generator, 200 kg chemical storage tank, 304–324 kW Li-ion battery storage and 299–335 kW converter combination is the optimal stand-alone configuration for the selected sites. The optimum cases' net present cost ranges between $2.53 M to $2.92 M, and the cost of electricity ranges between $0.285 to $0.329 per kWh. The proposed optimization methodology is suitable for applications in any location, considering the metrological conditions of the site under study. Other Information Published in: Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.energy.2021.123008